Fresnel Diffraction Strategy Enables the Fabrication of Flexible Superomniphobic Surfaces - Zhang, Zhonggang (Langmuir : the ACS journal of surfaces and colloids, 2022)
Doubly re-entrant surfaces inspired by springtails exhibit excellent repellency to low-surface-tension liquid. However, the flexible doubly re-entrant surfaces are difficult to fabricate, especially for the overhang of the structure. Herein, we demonstrate a simple Fresnel aperture diffraction modulation strategy in microscale lithography coupled with a molding process to obtain the flexible doubly re-entrant superomniphobic surfaces with nanoscale overhangs. The negative nanoscale overhang features were formed in a single-layer photoresist due to the fine-modulation of the optical intensity fluctuation of the Fresnel aperture diffraction. The as-prepared flexible non-fluorinated polydimethylsiloxane (PDMS) doubly re-entrant microstructure based on the Fresnel aperture diffraction (D-BF) surface (without any additional treatments) could repel ethanol droplets (21.8 mN m-1) in the Cassie-Baxter state. The robust nanoscale overhangs obtained by the molding process enable the maximum breakthrough pressure for the low-surface-tension ethanol droplets on the D-BF surfaces up to about 230 Pa, allowing ethanol liquids with Weber numbers up to 8.7 to fully bounce off. The fabricated non-fluorinated D-BF superomniphobic surface maintains outstanding liquid repellency after the surface wettability modification and deformation test